2013
DOI: 10.1242/jcs.129270
|View full text |Cite
|
Sign up to set email alerts
|

Late endosomal transport and tethering are coupled processes controlled by RILP and the cholesterol sensor ORP1L

Abstract: SummaryLate endosomes and lysosomes are dynamic organelles that constantly move and fuse to acquire cargo from early endosomes, phagosomes and autophagosome. Defects in lysosomal dynamics cause severe neurodegenerative and developmental diseases, such as Niemann-Pick type C disease and ARC syndrome, yet little is known about the regulation of late endosomal fusion in a mammalian system. Mammalian endosomes destined for fusion need to be transported over very long distances before they tether to initiate contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
161
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(168 citation statements)
references
References 54 publications
7
161
0
Order By: Relevance
“…We previously showed that expression levels of these tagged proteins in our systems are low (comparable to endogenous) and that the tagged subunits incorporate into functional complexes (30).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…We previously showed that expression levels of these tagged proteins in our systems are low (comparable to endogenous) and that the tagged subunits incorporate into functional complexes (30).…”
Section: Resultsmentioning
confidence: 86%
“…Constructs-RAB7 and RILP (29) and full-length VPS constructs and GFP-VPS33b L30P (30)have been described previously. GFP-VPS16 and GFP-VPS18 were gifts from Chengyu Liang (Department of Molecular Microbiology and Immunology, University of Southern California, Los Angeles).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Interestingly, 2 recent studies have shown that late endosomal Rab7 effector Rab-interacting lysosomal protein (RILP) that binds to the dynein adaptor, dynactin, also interacts with subunits of the HOPS complex. 48,49 These findings suggest a model whereby Rab7-RILP and Arl8b-SKIP both interact with HOPS complex and play opposing roles in regulating positioning of HOPS endosomes by mediating their association with motor proteins (Fig. 4).…”
Section: Arl8b Regulates Lysosomal Motility Through Interaction With mentioning
confidence: 89%
“…Our current study reveals that a strong candidate to mediate this stimulation is the single fly BICD protein, which is known to be one of a small number of proteins recruited to the RNA element (Dix et al , 2013). It will be important to determine in the future whether other BICD family members such as BICDR proteins (Schlager et al , 2010) and unrelated cargo adaptors for dynein (Engelender et al , 1997; Horgan et al , 2010; van der Kant et al , 2013; van Spronsen et al , 2013) also regulate motor processivity by promoting the interaction with dynactin.…”
Section: Discussionmentioning
confidence: 99%